The aquatic communities inhabiting internodes of two sympatric bamboos in Argentinean subtropical forest - Campos, Raul Ernesto (2013)
To determine if phytotelmata of sympatric bamboos of the genus Guadua might be colonized by different types of arthropods and form communities of different complexity the following objectives were formulated: to analyze the structure and species richness of the aquatic macroinvertebrate communities; to analyze comparatively co-occurrences comparatively and to identify the main predators. Field studies were conducted in a subtropical forest in Argentina where eighty water-filled bamboo internodes of Guadua chacoensis and G. trinii were sampled. Morphological measurements indicated that G. chacoensis holds more fluid than G. trinii. The communities differed between Guadua species, but many macroinvertebrate species used both phytotelmata. These phytotelmata were mainly colonized by Diptera of the families Culicidae and Ceratopogonidae.